The role impairment associated with mental disorder risk profiles in the WHO World Mental Health International College Student Initiative - Alonso, J.; Vilagut, G.; Mortier, P.; Auerbach, R.; Bruffaerts, R.; Cuijpers, P.; Demyttenaere, K.; Ebert, D.; Ennis, E.; Gutiérrez-García, R.; Green, J.; Hasking, Penelope; et al. (John Wiley & Sons, 2018)
© 2018 John Wiley & Sons, Ltd. Objective: The objective of this study is to assess the contribution of mental comorbidity to role impairment among college students. Methods: Web-based self-report surveys from 14,348 first-year college students (Response Rate [RR] = 45.5%): 19 universities, eight countries of the World Mental Health International College Student Initiative. We assessed impairment (Sheehan Disability Scales and number of days out of role [DOR] in the past 30 days) and seven 12-month DSM-IV disorders. We defined six multivariate mental disorder classes using latent class analysis (LCA). We simulated population attributable risk proportions (PARPs) of impairment. Results: Highest prevalence of role impairment was highest among the 1.9% of students in the LCA class with very high comorbidity and bipolar disorder (C1): 78.3% of them had severe role impairment (vs. 20.8%, total sample). Impairment was lower in two other comorbid classes (C2 and C3) and successively lower in the rest. A similar monotonic pattern was found for DOR. Both LCA classes and some mental disorders (major depression and panic, in particular) were significant predictors of role impairment. PARP analyses suggest that eliminating all mental disorders might reduce severe role impairment by 64.6% and DOR by 44.3%. Conclusions: Comorbid mental disorders account for a substantial part of role impairment in college students.